2019
DOI: 10.1002/ecy.2821
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood effects explain increasing asynchronous seedling survival in a subtropical forest

Abstract: Biotic interactions play a critical role in mediating community responses to temporal environmental variation, but the importance of these effects relative to the direct effects of environmental change remains poorly understood, particularly in diverse forest communities. Here we combine a neighborhood modeling approach with insights from coexistence theory to assess the effects of temporal variation in species interactions and environmental conditions (e.g., precipitation, temperature, and understory light av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…The influence of internal dynamics is widely viewed as a key reason for the difficulty in predicting local diversity change (Chen et al, 2019; McGill et al, 2015). The four types of interaction topologies detailed above—dominance, facilitation, negative frequency, and positive feedback—are common expectations for contrasting structures that can enable generalization of internal dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of internal dynamics is widely viewed as a key reason for the difficulty in predicting local diversity change (Chen et al, 2019; McGill et al, 2015). The four types of interaction topologies detailed above—dominance, facilitation, negative frequency, and positive feedback—are common expectations for contrasting structures that can enable generalization of internal dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Although biotic interactions also can have important impacts on seedling demography (e.g. competition, herbivory or plant–pathogen associations [Alexander et al., 2015; Chen, Swenson, et al., 2019; Chen, Wang, et al., 2019; Ibáñez et al., 2013; Uriarte et al., 2018]), these effects are largely negative (but see Corrales et al. (2018) on mycorrhizal associations).…”
Section: Discussionmentioning
confidence: 99%
“…Important mechanisms, such as ontogenetic variations in trait‐mediated demography (Green & Harms, 2018) and episodic recruitment events driven by climatic oscillations (Brown & Wu, 2005; Pederson et al., 2014), have been identified that may determine both the percentage of survivors of the seedling phase and the amount of time it takes to pass through this phase, critical to how we anticipate the temporal scales in forest regeneration. These life‐history processes make the demographic behaviour of species' seedling populations an important focus for explaining species coexistence and forest dynamics (Comita et al., 2010; Green et al., 2014), density‐dependent processes (Comita et al., 2014), the role of pests and pathogens in defining tree communities (Bagchi et al., 2014; Chen, Swenson, et al., 2019; Chen, Wang, et al., 2019), the spatial influence of forest structure on populations (Comita & Engelbrecht, 2009; Johnson et al., 2017) and trait‐based life‐history strategies (Jia et al., 2020; Umaña et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These novel interactions have the potential to affect species' performance in surprising ways. For example, experimental range expansion of Florida mangrove seedlings into mature mangrove habitat showed species‐specific direct effects of canopy microclimate on seedling survival and indirect effects of herbivore damage, driven by microclimate (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%